THE IMPACT OF AERIAL YOGA ON FLEXIBILITY AND BALANCE IN SPORTS PERSON: EXPLORATORY STUDY - Dr. R. RAMAKRISHNAN,; Dr. T. PARASURAMAN,; Dr. D. HARIGARAN,; Dr. C. Vijayalakshmi,; PRIYADARSHINI S, (The Bioscan, 2024)
This preliminary investigation exploresthe impact of a 8-week aerial yoga program on flexibility and balance in athletes aged 18 to 25. Sixty sports players from the Hindustan Institute of Technology and Science, Padur, Chennai, were randomly assigned to either an intervention group (n=30) and non intervention group (n=30). The intervention group participated in three weekly 60-minute aerial yoga sessions led by certified instructors, while the non intervention group refrained from engaging in any specific activity. Flexibility and balance were assessed using the sit-and-reach test and one- leg stand test, respectively, before and after the intervention. Descriptive statistics summarized participant characteristics, paired t-tests assessed pre- and post-intervention changes within groups, and ANCOVA evaluated differences between groups. The results indicated significant improvements in flexibility and balance in the intervention group, emphasizing the potential benefits of aerial yoga for sports players. Acknowledgements: This study was financially supported by the Hindustan SEED MONEY grant, provided by Hindustan Institute of Technology and Science, Chennai, Tamil Nadu.